1914–2014: never again. (1st July 2013) - Jacobs, Howy
Abstract : The coming year marks the centenary of the events that lead to the global catastrophe of July 1914. Howy appeals for a worldwide movement to prevent any possibility of such a disaster occurring in today‧s equally unstable world.